2002
DOI: 10.1038/sj.bmt.1703338
|View full text |Cite
|
Sign up to set email alerts
|

Healthy sibling donor anxiety and pain during bone marrow or peripheral blood stem cell harvesting for allogeneic transplantation: results of a randomised study

Abstract: Summary:This study reports the first comparison of healthy donor subjective well-being during two alternative procedures of hematopoietic stem cells harvesting for allogeneic transplantation. Among the 105 donors included between September 1996 and October 1998 in the SFGM French randomised trial aiming to compare allogeneic bone marrow (BM) transplantation and blood cell (BC) transplantation, 64 donors (33 in BC and 31 in BM groups) were relevant for the analysis. They had received a set of self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…Takita et al 16 , in a case report, described the stress experienced by a sibling who was not HLA matched with her ill sister. Earlier studies have shown that sibling stem cell donors are in a vulnerable situation, [3][4][5][6]12,13,17,18 and the survey findings indicate that this is also true of siblings who are unable to donate. A suggestion is that all HLA typed potential sibling donors should receive the typing results through personal contact with health professionals, and that they should receive it before the patient.…”
Section: Discussionmentioning
confidence: 86%
“…Takita et al 16 , in a case report, described the stress experienced by a sibling who was not HLA matched with her ill sister. Earlier studies have shown that sibling stem cell donors are in a vulnerable situation, [3][4][5][6]12,13,17,18 and the survey findings indicate that this is also true of siblings who are unable to donate. A suggestion is that all HLA typed potential sibling donors should receive the typing results through personal contact with health professionals, and that they should receive it before the patient.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study (9) had already demonstrated that the depreciation of the quality of life and physical health of the recipient causes an adverse impact on the life of the related donor. It is confirmed, therefore, that the physical conditions of the recipient are associated with the emotional reactions to the donor (4) .In relation to the experience of donating bone marrow, where literature is still very restricted, it is perceived that the act of donating brings diverse psychological implications for donors: before the donation in the form of anxiety (10)(11) , immediately after the process, due to the influence of psychological factors and years elapsed, as changes arising in the quality ofThere is a shortage of studies dedicated to evaluating the experience and subjective implications of donating bone marrow for the related donor. This study aims to reduce this gap.…”
mentioning
confidence: 79%
“…Earlier studies have shown that sibling donors are in a vulnerable situation (Bredeson et al, 2004;Fortanier et al, 2002;Wiener et al, 2008;Williams et al, 2003), and Study II indicates that this is true even for siblings who are unable to donate. This has also been shown in a case study (Takita et al, 2011) describing the stress experienced by a sibling who did not HLA match her ill sister.…”
Section: Information and Care Of Potential Sibling Donorsmentioning
confidence: 97%
“…The harvesting takes place at the surgery theatre and usually the donor stays in hospital for 2-3 days. The most common and transient side-effects of bone marrow harvesting are fatigue, lower back pain and pain at the site where the needles were inserted, and nausea from the sedation (Fortanier et al, 2002;Switzer et al, 2001).…”
Section: Donationmentioning
confidence: 99%
See 1 more Smart Citation